2011
DOI: 10.1371/journal.pgen.1001342
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Phylogeny of Living Primates

Abstract: Comparative genomic analyses of primates offer considerable potential to define and understand the processes that mold, shape, and transform the human genome. However, primate taxonomy is both complex and controversial, with marginal unifying consensus of the evolutionary hierarchy of extant primate species. Here we provide new genomic sequence (∼8 Mb) from 186 primates representing 61 (∼90%) of the described genera, and we include outgroup species from Dermoptera, Scandentia, and Lagomorpha. The resultant phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

189
1,368
22
31

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,206 publications
(1,610 citation statements)
references
References 77 publications
(104 reference statements)
189
1,368
22
31
Order By: Relevance
“…From this it was proposed that LCVs have coevolved with the host, but some evidence of interspecies virus transfer was also apparent (63,64). The extensive differences between ma-EBNA1 and hu-EBNA1 (outside of the Cterminal domain) suggest that EBNA1 has undergone subfunctionalisation since the separation of Old and New World primates 43 MYA.…”
Section: Discussionmentioning
confidence: 99%
“…From this it was proposed that LCVs have coevolved with the host, but some evidence of interspecies virus transfer was also apparent (63,64). The extensive differences between ma-EBNA1 and hu-EBNA1 (outside of the Cterminal domain) suggest that EBNA1 has undergone subfunctionalisation since the separation of Old and New World primates 43 MYA.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier analyses of morphological and molecular data, all supported that the African colobine forms a monophyletic clade [1,12,19], grouping Piliocolobus, Procolobus, and Colobus together [17][18][19][24][25][26]29,30] (Figure 3). Interestingly, a recent phylogenetic analyses of 83 mobile elements from Roos et al [19] indicated a closer association of the Procolobus/Piliocolobus clade to Asian colobines than to Colobus, a relationship that was not rejected by nuclear sequence data in their study, leading them to propose African colobines paraphyly hypothesis ( Figure 3(e)).…”
Section: Phylogeny Of African Colobinaementioning
confidence: 88%
“…In comparison, Figure 3 Hypotheses of phylogenetic relationships among Colobine genera. Trees were reconstructed based on (a) 12 protein-coding mt genes (10 kb) [17]; (b) fragment of X-chromosome (4.3 kb) [26] and 54 nuclear genes (35 kb) [18]; (c) complete cytb gene (1.8 kb) [30] and 7 mt genes (6.1 kb) [29]; (d) 15 mt genes and 43 nuclear genes (42 kb) [25], 44 nuclear non-coding genes (23 kb) [31]; (e) 83 mobile elements [19]; (f) nuclear genes (13 kb) [19]; (g) complete mt genomes (16.5 kb) [31].…”
Section: Phylogeny Of Asian Presbytinamentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the chromosome complement of Neotropical primates (NP) underwent a dramatic karyotypic shuffling during the evolutionary divergence of these species (Stanyon et al., 2008), which took approximately 40 million years (Perelman et al., 2011; Schrago, 2007). Differently from hominids, chromosome diploid number varies sharply in NP, ranging from 16 in Callicebus lugens (Bonvicino et al., 2003) to 62 in Brachyteles arachnoides and Lagothrix lagotricha .…”
Section: Introductionmentioning
confidence: 99%